MICROBIOLOGICAL SUBSTANTIATION OF THE CHOICE OF PHARMACOLOGICAL GROUPS OF ANTIBACTERIAL DRUGS IN THE TREATMENT OF ABDOMINAL SEPSIS AGAINST THE BACKGROUND OF DIABETES MELLITUS - Korikhonov, D.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The problem of treatment of purulent-septic complications is associated with a steady increase in the resistance of the main pathogens to the antibacterial drugs used, while the profile of antibiotic resistance may have pronounced regional characteristics. In this regard, it is relevant to use clinical and pharmacological approaches to the development of an algorithm for the selection of antibacterial drugs based on the results of studying the etiological structure and local data of pathogen resistance. Material and methods. A retrospective and prospective analysis of the results of the treatment of 105 patients with abdominal sepsis for the period 2013-2022 was carried out. The main group (n=42) included all patients with abdominal sepsis with diabetes mellitus and the control group (n=63), included all patients with abdominal sepsis without diabetes mellitus who met the principles of inclusion criteria. Results. Most often, the structure of the causative agents of purulent-septic complications in patients with diabetes mellitus is represented by multidrug-resistant microorganisms: E. coli, Klebsiella spp., fungi of the genus Candida, Proteus spp. Conclusion. In the schemes of empirical initial therapy of purulent-septic complications against the background of diabetes mellitus, it is advisable to use combinations of 3-4 generation cephalosporins, amoxicillin/clavulanate, 3rd generation fluoroquinolones with metronidazole as first-line agents. With the development of septic shock, carbapenems in combination with Glycopeptide or Oxazolidinone are most effective as first-line antibiotics.